Nutritional Status on the Cognitive Development of Early Childhood (5-6 Years) at TKQ/TPQ Al hafiz Medan - Maimunah. R; Yunita, Wilda; Ramadhani, Yuni (International Journal of Public Health Excellence (IJPHE), 2024)
Research purposes are analyzing nutritional status, stimulation, psychosocial factors, and influencing factors in cognitive development in preschool children. Study This was carried out in Babakan Village, District Dramaga, Bogor Regency, West Java. Study This cross-sectional design was done with respondents mothers who have children ages 3–5 years old. Fifty-eight children are involved. Spread-level education Mother Of the various percentages, the largest (44.8%) had a high school education. About 78% of per capita income families are classified as not poor and 22.4% are in the poor category. The average score of knowledge nutrition for mothers amounted to 76.7 ± 2.5 (the category currently). Most of the child preschools (84.4%) have score stimulation psychosocial in category medium (30-45). Nutritional status of toddlers showed that 15.5% of toddlers were underweight, 5.2% were underweight, 3.4% were severely underweight, and 19% of children entered the categories of short and very short (stunted). Regression results gradually show that stimulation psychosocial (P<0.001), participation in early childhood education (P = 0.002), and nutritional status based on index height against age (P = 0.028) had an effect positive and significant on the development of cognitive child preschool (adjusted R2, 0.434; P = 0.028).